Pengaruh Pemberian Ekstrak Daun Salung (Psychotria viridiflora) terhadap Glukosa Darah Mencit (Mus musculus) - Niki Dwi Dia Dara; Aceng Ruyani; Rendy Wikrama Wardana; Afrizal Mayub; Bhakti Karyadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aimed to determine the effect of salung (Psychotria viridiflora) leaf extract on blood glucose levels in hyperglycemic mice (Mus musculus). A total of 25 mice weighing 20–40 grams were divided into five treatment groups: P1 (negative control: feed and distilled water), P2 (alloxan 10 mg/kg BW + glibenclamide 0.1 mg/kg BW), P3 (alloxan 10 mg/kg BW + P. viridiflora leaf extract 0.0112 g/kg BW), P4 (alloxan 10 mg/kg BW + P. viridiflora leaf extract 0.0225 g/kg BW), and P5 (alloxan 10 mg/kg BW + P. viridiflora leaf extract 0.0337 g/kg BW). Blood glucose levels were measured four times—on days 0, 6, 12, and 18—covering baseline measurement, post-alloxan induction, and after treatment administration. The results showed that the highest dose (0.0337 g/kg BW) was the most effective in reducing blood glucose levels in alloxan-induced mice, with an effect comparable to the standard drug glibenclamide. In conclusion, P. viridiflora leaf extract has potential as an alternative herbal antidiabetic therapy in M. musculus. Keywords: Antidiabetic, Blood Glucose, Extract Leaf, Hyperglycemia, Mus musculus, Psychotria viridiflora